Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER) dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2021 - Riski, Fildzatu; Sudarsono, Bambang (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to determine the effect of Earning Per Share (EPS), Price Earning Ratio (PER) and Return On Equity (ROE) on stock prices in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population used in this study were Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period as many as 83 companies with sampling using the purposive sampling method and 26 companies were selected as samples in the study. The analytical method in this research uses multiple linear regression. The results of this study indicate that Earning Per Share (EPS) has a positive effect on stock prices, this is evidenced by the t count value of 10.849 and t table of 1.982 with a significance value of 0.000 where the t count t table and sig value 0.05. The Price Earning Ratio (PER) variable has a positive effect on stock prices, this is evidenced by the t count value of 3.781 and t table of 1.982 with a significance value of 0.000 where the t count t table and sig value 0.05. The variable Return On Equity (ROE) has a negative effect on stock prices, this is evidenced by the t count value of -8.882 and t table of 1.982 with a significance value of 0.000 where the t count t table and sig value 0.05. Simultaneously the variables Earning Per Share (EPS), Price Earning Ratio (PER) and Return On Equity (ROE) have a positive effect on stock prices as evidenced by the f value of 54.224 and f table of 2.69 with a significance value of 0.000 where the t value is calculated t table and sig value 0.05.